Education (in time) Full: the Program More Education in a rural school in the municipality of Corumbá/MS - Geraldo Garbelini Neto; Anamaria Santana da Silva (Universidade Federal do Norte do Tocantins, 2019)
This article is part of the Master's researchi carried out with the Postgraduate Program in Education, Federal University of Mato Grosso do Sul, Pantanal Campus. The objective is to analyze how educational practices in the More Education Program (MEP) in relation to the proposal that regulates the Articulation "For an Education of the Rural" and that present themselves as contradictions in the reality of the school of the rural in the municipality of Corumbá/MS, that refers an implantation of the Program and execution of its educational activities. In the course of the research we seek to near both educational proposals: Rural Education (RE) and Integral Education (in time). The empirical research consisted of interviews: with school management (01), pedagogical coordination (02), and monitors (05) who ministered to educational activities. The results show that the documents of RE and MEP were on the margins of the process of materialization of this educational proposal, just as it didn't happen on the basis of the reflections of scholars in the area.